2022
DOI: 10.1021/acs.est.2c02632
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Removal of Low-Concentration Uranium Using TiO2 Nanotube Arrays/Ti Mesh Electrodes

Abstract: Groundwater containing naturally occurring uranium is a conventional drinking water source in many countries. Removal of low concentrations of uranium complexes in groundwater is a challenging task. Here, we demonstrated that the TiO2 nanotube arrays/Ti (TNTAs/Ti) mesh electrode could break through the concentration limit and efficiently remove low concentrations of uranium complexes from both simulated and real groundwater. U­(VI) complexes in groundwater were electro-reduced to UO2 and deposited on the TNTAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 36 publications
(59 reference statements)
0
11
0
Order By: Relevance
“… , As time goes by, the binding energy of Fe–SO 4 2– bonds moves to a lower direction at about 0.9 eV, which may be attributed to the strong chemical interaction between Fe–SO 4 2– bonds and UO 2 2+ due to the formation of U­(VI)–sulfate surface complexes . For O 1s XPS spectra of S-NRI, the peaks at 535.6, 531.7, and 530.3 eV are considered as adsorbed water, M–OH bonds, and metal oxide (M–O bonds), respectively (Figure c). ,, As the reaction progresses, the content of O1 (M–O bonds) gradually increases, confirming that uranium oxide has been extracted onto the S-NRI surface, while the content of O2 (M–OH bonds) and O3 (adsorbed H 2 O) gradually decreases (Figure c,f and Table S1). Compared with the original S-NRI, due to the chemical interaction between Fe–OH and UO 2 2+ , the peak position of M–OH bonds after EUE shifted to the direction of low binding energy by about 0.58 eV (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… , As time goes by, the binding energy of Fe–SO 4 2– bonds moves to a lower direction at about 0.9 eV, which may be attributed to the strong chemical interaction between Fe–SO 4 2– bonds and UO 2 2+ due to the formation of U­(VI)–sulfate surface complexes . For O 1s XPS spectra of S-NRI, the peaks at 535.6, 531.7, and 530.3 eV are considered as adsorbed water, M–OH bonds, and metal oxide (M–O bonds), respectively (Figure c). ,, As the reaction progresses, the content of O1 (M–O bonds) gradually increases, confirming that uranium oxide has been extracted onto the S-NRI surface, while the content of O2 (M–OH bonds) and O3 (adsorbed H 2 O) gradually decreases (Figure c,f and Table S1). Compared with the original S-NRI, due to the chemical interaction between Fe–OH and UO 2 2+ , the peak position of M–OH bonds after EUE shifted to the direction of low binding energy by about 0.58 eV (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…At present, electrochemical uranium extraction (EUE) has shown great potential due to its large adsorption capacity and fast adsorption rate. The pulse electrochemical method can effectively realize the redistribution of uranium ions on the electrode surface, improve the selectivity of uranium ions, and show a large adsorption capacity. , However, these electrochemical strategies still face the challenge of high cell voltage, and it is difficult to balance cell voltage, adsorption capacity, and selectivity, especially in the complex seawater environment. Our previous research has confirmed that electrochemically mediated Fe­(II)/Fe­(III) redox-coupled uranium extraction can significantly reduce the cell voltage of EUE . How to strengthen the Fe­(II)/Fe­(III) redox cycle process to achieve the rapid electron transfer and regeneration of active sites and how to regulate the surface structure to enhance the selective adsorption ability of uranyl ions are crucial for EUE.…”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, it is vitally important to identify substrates with distinctive structural characteristics to combine catalytic materials effectively. A variety of conductive substrates (nickel foam, 10 TiO 2 , 11 and carbon cloth 12 ) are widely mentioned in this field. TiO 2 as a semiconductor metal oxide makes it easy to synthesize the TiO 2 -NTs (TNTs) structure with adjustable shape, in which tubular structures are considered the most suitable method for achieving more significant surface area increases without increasing the geometric area.…”
Section: Introductionmentioning
confidence: 99%
“…Electro-assisted uranium extraction, as a fresh technology, provides a new insight into uranium extraction from wastewater or seawater because of the accelerated extraction kinetics driven by the electric field and selectivity for nonreductive coexisting ions. For instance, Liu et al employed an electrochemical approach utilizing amidoxime-functionalized carbon electrodes for uranium extraction from seawater . However, the removal and extraction of uranium from fluorine-containing uranium wastewater using the electrochemical reduction method still present challenges and knowledge gaps.…”
Section: Introductionmentioning
confidence: 99%